Parvovirus RNA Processing: Compact Genomic Organization and Unique Alternative mRNA Processing Mechanisms - Lisa K. Uhl; Olufemi O. Fasina (Viruses)
Parvoviruses have compact genomic organizations with overlapping open reading frames and thus utilize alternative RNA processing strategies, alternative splicing, alternative polyadenylation, and alternative translation mechanisms to generate a range of diverse proteins encoded within their genome. This comprehensive review provides an update on recent insights into the diverse mRNA processing mechanisms utilized by members of the Parvoviridae family, with emphasis on Bocaparvoviruses and Dependoparvoviruses to expand their protein repertoire and maintain their replicative advantage in infected host cells. It highlights the role of Bocaparvovirus ancillary nonstructural protein NP1; the first parvovirus protein involved in mRNA processing, specifically alternative splicing and alternative polyadenylation.